Gabon : 2006 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2006)
Gabon continues to enjoy record high oil prices, buoying both exports and government revenues. The critical medium-term challenge facing Gabon is managing the transition from an economy highly dependent on oil to a diversified economy that harnesses private sector initiative, and makes decisive progress in poverty reduction. The fiscal policy stance requires significant tightening. Raising economic growth and reducing poverty necessitate the acceleration of the structural reform agenda. Fostering transparency is a key ingredient to strengthening governance and accountability in Gabon.